Spatial structure of industry according to R&D intensity during the economic crisis. An example of changes taking place in the Krakow and Wroclaw agglomerations during 2018–2021 - Brezdeń, Paweł; Sikorski, Dominik; Smętkiewicz, Karolina (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2023)
The contemporary development of the knowledge-based economy makes it extremely important to analyze and evaluate the structures of the economy in terms of its degree of modernity. Hence, in periods of economic downturn, research relating to the innovativeness of business entities acquires particular importance in the perspective of the conditions of the economic development process. The purpose of the study was to analysis and assess spatial changes in the distribution of processing industry entities due to the level of its innovation in two Polish agglomerations (Kraków and Wrocław) in 2018-2021, i.e. covering mainly the period of the Covid-19 pandemic crisis. Changes in the spatial structure of the industry were presented using the classification of industrial processing according to R&D intensity in the system of high, medium-high, medium-low and low technology, both in static and dynamic terms. Quantitative methods were used to analysis and identify the degree of concentration and spatial specialization of the industry. The conducted research showed that the economic downturn resulting from the aforementioned crisis had little impact on the studied phenomenon. The changes recorded were analogous to the changes from previous years. The only exception were different trends in the distribution of low-tech industrial entities. Perhaps the consequences of the existing economic conditions resulting from the pandemic period will become visible only in the longer term.